2004
DOI: 10.1159/000080309
|View full text |Cite
|
Sign up to set email alerts
|

Extra-Esophageal Disorders in Gastroesophageal Reflux Disease

Abstract: Gastroesophageal reflux disease (GERD) is a common condition that effects about 10% of the adult population comprising a broad spectrum of symptoms and varying degrees of severity and frequency. Extra-esophageal manifestations are increasingly being recognized. Up to 50% of patients with an endoscopically proven or negative esophagitis suffer from symptoms other than heartburn or acid regurgitation such as laryngitis, hoarseness, chronic cough, asthma, or non-cardiac chest pain. The therapy of choice is proton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 30 publications
0
14
0
1
Order By: Relevance
“…A major advance in the understanding of extra-esophageal manifestations comes from the recognition that a significant number of patients with asthma or chronic cough, particularly if it is nocturnal, have gastroesophageal reflux as a trigger. [1] Extra-esophageal symptoms of GERD are highly prevalent among patients with both frequent and infrequent typical GERD symptoms.…”
Section: Pulmonary Manifestations Of Gerdmentioning
confidence: 99%
See 2 more Smart Citations
“…A major advance in the understanding of extra-esophageal manifestations comes from the recognition that a significant number of patients with asthma or chronic cough, particularly if it is nocturnal, have gastroesophageal reflux as a trigger. [1] Extra-esophageal symptoms of GERD are highly prevalent among patients with both frequent and infrequent typical GERD symptoms.…”
Section: Pulmonary Manifestations Of Gerdmentioning
confidence: 99%
“…The kind of GERD disease, weight and gender did not have significant relationship with asthma. [1] A recent systematic review[3] of 28 epidemiological studies found a 59.2% weighted average prevalence of GERD symptoms in asthmatic patients, compared to 38.1% in controls. The corresponding prevalence of asthma in GERD patients was 4.6%, compared to 3.9% in controls.…”
Section: Prevalencementioning
confidence: 99%
See 1 more Smart Citation
“…Certain extra-oesophageal symptoms may be associated with gastro-oesophageal reflux, leading to presentation to respiratory physicians (with cough and wheeze) and ear, nose, and throat specialists (with hoarseness and laryngitis. 1 Although often related to meals, oesophageal chest pain can also be precipitated by emotion and exercise-qualities that mimic the symptoms of angina pectoris attributable to ischaemic heart disease (IHD). Furthermore, a number of the risk factors for the development of coronary disease, such as cigarette smoking, obesity, and diabetes, also increase the likelihood of oesophageal disorders, and medical treatments of angina often have beneficial effects on oesophageal symptoms.…”
mentioning
confidence: 99%
“…Extraesophageal manifestations of GERD have progressively attracted attention during the past decade. GERD has been associated with asthma, chronic cough, hoarseness, otitis media, atypical loss of dental enamel, idiopathic pulmonary fibrosis, recurrent pneumonia, chronic bronchitis and even sudden infant death syndrome [5][6][7][8][9]. GERD originates from a disturbance in the function of the lower esophageal sphincter (LES) including anatomical and physiological aspects [10] with regurgitation of food and acid into the esophagus.…”
Section: Introductionmentioning
confidence: 99%